PENGARUH FRAKSI VOLUME PADA GREEN COMPOSITE SERAT BAMBU DENGAN MATRIKS SARI PATI KENTANG TERHADAP PENYERAPAN SUARA DAN POROSITAS - Pratama, Ferdy Gilang; Kencanawati, Cok Istri Putri Kusuma; Negara, Dewa Ngakan Ketut Putra (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract This research discusses the effect of volume fraction in green bamboo fiber composite with a matrix of potato starch on sound absorption and porosity. The Green Composite materials used are bamboo fiber as reinforcement and potato starch as the matrix. Tube impedance and porosity testing are research methods used in accordance with ASTM (American Standard Testing Material). The data obtained was tested using an impedance tube equipped with Audacity software and an NCH Tone generator with an input frequency of 400 Hz - 4000 Hz. The research results showed that there was an influence of the volume fraction of bamboo fiber on the porosity of the specimen, but it was not significant on the sound absorption ability. The highest sound absorption coefficient value was obtained at a of 400 Hz frequency of0.65, which is equivalent to 4.55 dB Sound Reduction Index (ISO 140-3). The specimens with a 10% fiber volume fraction have the highest porosity at 25.39%. This research is expected to provide a solution to reducing noise. Keywords : Green Composite, Bamboo Fiber, Potato Starch Extract, Acoustic Testing, Porosity, Fiber Volume Fraction, Tube Impedance, Sound Absorption